Matching teaching styles and learning styles: what happens in the case of a mismatch? - Lee, Mei Ph’ng; Thang, Siew Ming; Radha M. K. Nambiar (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
It has been acknowledged that teacher and student diversity in the classroom have led to varied teaching and learning styles preferences. Previous studies have generally looked at teaching styles or learning styles in isolation and have rarely considered the impact of teaching styles on learning styles or vice versa. This study extends this one step further by first establishing the learning styles of a group of engineering students and then investigating the impact of the teaching styles of their Technical Communication teacher on them in an English for Specific Purposes (ESP) context. Specifically it explores whether accommodation or resistance arises when there is a mismatch in teaching and learning styles. The respondents were 5 Malaysian engineering undergraduates from two engineering faculties of a public university. Data from students were collected using Felder and Silverman’s Index of Learning Styles (ILS) questionnaire, student interviews and reflective journals. Teaching styles of the teacher were identified using Grasha and Reichmann’s Teaching Style Survey. The findings revealed that the students and the teacher have mixed learning styles and teaching styles preferences respectively. In addition, the teachers’ teaching styles generally have a positive impact on the students but there were occasions when these were not so. These findings will be discussed in greater detail in this paper.